Moon! : [book with audioplayer] Earth's best friend - McAnulty, Stacy (McAnulty, Stacy. Our universe., 2020)
"A light-hearted nonfiction picture book about the formation and history of the moon and its history in relation to earth--told from the perspective of the moon itself!"--